OpenFOAM simulation of turbulent flow in a complex dam structure - Bai, Di; Muhammad, Noor; Shah, Nehad Ali; Ali, Bagh; Raju, C. S. K.; Wakif, Abderrahim; Ramesh, G. K.; Ahmed, Shams Forruque; Madhukesh, J. K.; Madhu, J.; Prasannakumara, B. C.; Sarris, I. (Indian journal of physics, 2024)
The economic and environmental benefits of dam flow need to be calculated theoretically using open-source field operation and manipulation (OpenFOAM). The potential consequences of a hypothetical dam failure depend mainly on the kind of collapse and the reservoir’s capacity. Riverbed singularities develop during floods and change over time, affecting the dam-break pulse and the shape of hydrographs. Three-dimensional simulators are commonly used to detect incremental variations in dam-break flow. However, physical obstructions or quick changes in the bed channel’s characteristics can significantly alter flood propagation and scenarios. To reduce damage to the spillway, flow speed is analyzed, and obstructions in the spillway bed are taken into account. Large eddy simulation is used to explain turbulent flow behavior on the dam spillway. The kinetic energy in a turbulent flow is determined at the input, obstructions, and exit. Using C++ programming and OpenFOAM simulation, velocity and turbulent kinetic energy calculations are shown graphically. The results of the study demonstrate a remarkable alignment with the previously documented findings, which adds to the credibility and validity of our research.